A Fusion Rule-Based Adaptive Clustering Cooperative Spectrum Sensing Algorithm - Gongan Qiu; Sen Feng (Dianxin kexue)
A fusion rule-based adaptive clustering cooperative spectrum sensing algorithm was proposed for meeting the dynamic wireless channe1. Firstly，according to the integration rules of the fusion center，the SNR thresholds of clustering cooperative spectrum sensing model was deduced to satisfy the basic requirements of cognitive radio system. Then，the cluster heads detect the current channel state. They perform the cluster spectrum detection when the instantaneous SNR are better than their SNR thresholds. And they transmit the results to the fusion center for achieving cluster collaboration. Otherwise，all of the CR nodes would perform the spectrum detection in the cluster and send their results to the fusion center respectively. Or they would not participate to detect the spectrum holes and only receive the decision from the fusion center. Finally，the global decision will be made in the fusion center through fusing the detection results of the cooperative nodes. The simulation results show that the proposed algorithm can greatly improve the reports channel resources efficiency under the OR rule，while under the AND rule，the algorithm can expand the spectrum sensing system work range of about 30%，and can select the cluster nodes with high SNR to participate in cooperative spectrum sensing algorithm.